Kesalahan Berbahasa: Sebuah Analisis dan Implementasi dalam Penelitian Bahasa Arab - Muhammad Dzakiruddin; Junaedi Junaedi (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2022)
Understanding theory and the basis of research, sometimes considered as a matter that can be ruled out by referring to the framework of previous studies that already existed. This research aims to provide a description of the theory and basis in conducting language error analysts and their implementation in Arabic language research. This research is qualitative research with a literature study approach. The main data sources are journals that contain analysis studies of language errors. The second data source is a supporting document that is still related to this study. Data collection using documentary method. Analyze the data using descriptive analysis. The results showed the theory of Corder, Gas Morever, Selingker, Rusydi, and al-Rajih}i in the analysis of language errors, the existence of five basic in conducting analysis of language errors, and the existence of two categories in implementing language error analysis in Arabic language research. Findings of new theories and basic changes in research may occur, so as not to close the possibility of addition or reduction of theory and basis in the analysis of these language errors. Therefore, more research is always needed.